Analyzing the impact of sports education and psychological needs on kids’ educational outcomes- a machine learning approach - Najeh Rajeh Alsalhi; Abdellateef Abdelhafez Al Qawasmi; Salah Gad; Aras Al-Dawoodi; Ziyad Kamel Ellala; Soumaya Abdellatif; Iman Abed Rabou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Educators use standardized tests to assess children's ability to learn from other disciplines, such as neuroscience. By looking at this data, we can better understand how kids process and learn data and their ability to learn. This allows us to provide home and school support and specialized learning techniques. A child's development goes through stages from birth to adulthood. Children's growth and development are influenced by numerous factors, including their environment, genetics, and their culture. Kids find it difficult to express themselves, let alone examine their emotions. The field of child psychology can offer vital insight into this situation. Children's development is one of the ultimate goals of these professionals, who aim to improve parenting, child care, education, and psychotherapy by using that knowledge. Psychological and educational variables are removed to understand and research children's education. The modified support vector machine (SVM) method extracts information to predict whether educational and psychological factors influence a child's education. The research work is analyzed in a Java simulation environment, which proves that psychoanalysis based on MSVM has a stronger influence on children's studies.